Fundamentals of SARS-CoV-2 Biosensors - Herrington, Gaya (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
COVID-19 diagnostic strategies based on advanced techniques are currently essential topics of interest, with crucial roles in scientific research. This book integrates fundamental concepts and critical analyses that explore the progress of modern methods for the detection of SARS-CoV-2.